Incident sarcopenia in hospitalized older people: A systematic review. - Safiyyah Nurnajah Wan; Chiann Ni Thiam; Qi Xuan Ang; Julia Engkasan; Terence Ong (PLoS ONE, 2023)
Hospitalization has been associated with the development of sarcopenia. This study aimed to examine the new incidences of hospital sarcopenia, associated risk factors and health outcomes, as defined by internationally recognized diagnostic criteria in hospitalized older people. Pre-defined search terms were run through five databases. Six studies that assessed sarcopenia on two separate time points during hospitalization on older inpatients were included. Prevalence of sarcopenia varied from 14.1% to 55% depending on diagnostic criteria and cut-off points used. New sarcopenia occurred between 12% to 38.7% patients following hospitalization. Risk factors were older age, longer duration of bed rest, lower baseline body mass index, cognitive impairment and activities of daily living disability. None of the studies reported health outcomes associated with newly developed sarcopenia in hospital.